Enhancing Reading Motivation in a School Environment (การสร้างแรงจูงใจในการอ่านในสถานศึกษา) - เอี่ยมมงคลสกุล สรรพร; จาตุกัญญาประทีป ปัณณ์วิชญ์ (Journal of Behavioral Science for Development, 2014)
Reading skills are one of the most important tools for daily life and every student must learn and exercise them in order to attain a master of them. Students who have good reading skills will be able to benefit and learn more from various media. Therefore, motivation to read plays a very important role in encouraging students to engage in reading activities. In school, however, students do not have the opportunity to choose their reading materials. They have to restrict themselves to what is selected within the Basic Education Core Curriculum. This lack of autonomy, together with other factors such as low self-esteem, boredom in class, inability to perceive the value of the work, and low reading proficiency, is a major cause of students’ reading tasks avoidance. Teachers should change these attitudes by applying psychological strategies in order to motivate students towards improving their reading skills, not to attain a good grade but to master them. The expectation of extrinsic rewards is a fundamental problem of Thai students because without them, students will not read. As a result, reading behavior changes cannot occur. Recognizing the importance and necessity of cultivating good reading behaviors to students, we propose to introduce strategies to intrinsically motivate students to read, to cultivate regular reading habits, and to express their behavior from their internal needs, not for extrinsic rewards. Keywords: Reading, Motivation, Reading habit, Basic Education Core Curriculum บทคัดย่อ ทักษะการอ่านเป็นทักษะ “เครื่องมือ” ที่ต้องหมั่นฝึกฝนให้เกิดความชำนาญเพื่อใช้ประโยชน์ในชีวิตประจำวัน ผู้เรียนที่ “อ่านเป็น” จะสร้างองค์ความรู้ใหม่ได้หลากหลายและมีมุมมองที่กว้างขวางเพราะสามารถศึกษาข้อมูลจากสื่อ (Media) จำนวนมาก การมีทักษะการอ่านที่ดีเกิดจากการฝึกปฏิบัติอย่างสม่ำเสมอ แรงจูงใจจึงเป็นตัวแปรสำคัญที่เสริมสร้างการทำกิจกรรมดังกล่าวอย่างเป็นประจำ การอ่านในสถานศึกษาผู้เรียนไม่ได้มีอิสระอย่างเต็มที่ในการเลือกสิ่งที่ต้องการอ่านเพราะต้องอยู่ภายใต้กรอบที่กำหนดไว้เป็นมาตรฐานของประเทศ คือหลักสูตรแกนกลางการศึกษาขั้นพื้นฐาน การขาดอิสระนี้เองร่วมกับปัจจัยอื่น ๆ เช่น การขาดความเชื่อมั่นในตนเอง การรู้สึกเบื่อหน่ายบรรยากาศในชั้นเรียน การไม่เห็นคุณค่าของงานที่ทำ ความไม่สอดคล้องกันระหว่างสามัตถิยะ (Competence) ของผู้เรียนกับความยากง่ายของงานที่ต้องทำ เป็นต้น เหตุของการหลีกเลี่ยงการอ่าน ผู้สอนควรเปลี่ยนทัศนคติเหล่านี้ด้วยกลวิธีทางจิตวิทยาร่วมกับกลวิธีการสอนเพื่อให้ผู้เรียนฝึกทักษะการอ่านด้วยความพยายาม โดยคาดหวังว่าจะพัฒนาตนเองให้เป็นผู้มีความสามารถมิใช่เพียงเพื่อให้ได้คะแนน การคาดหวังรางวัลภายนอกนี้ถือเป็นปัญหาหลักของเยาวชนไทยในปัจจุบัน เพราะเมื่อไม่มีการกำหนดการวัดผลผู้เรียนก็จะไม่อ่าน ดังนั้นนิสัยรักการอ่านก็ไม่สามารถเกิดขึ้นได้ จากการตระหนักถึงความสำคัญและความจำเป็นของการปลูกฝังนิสัยรักการอ่านแก่เยาวชน ผู้เขียนขอเสนอแนะวิธีการสร้างแรงจูงใจภายในเชิงบวกที่ถือเป็นการปลูกฝังจิตสำนึกให้แสดงพฤติกรรมออกมาจากความต้องการของตนเองมิใช่จากการถูกบังคับหรือเพื่อได้รับผลตอบแทนภายนอก คำสำคัญ: การอ่าน แรงจูงใจ นิสัยรักการอ่าน หลักสูตรแกนกลาง